Nachhaltigkeitsberichterstattung in der Schweiz: Einordnung, Status quo und Ausblick - Reto Eberle; Peter Leibfried (Swiss Journal of Business)
While business indicators have been enriching financial reporting for quite a while, these indicators increasingly focus on sustainability issues. In spite of the fact that various international standards having been developed therefore, and are being applied voluntarily by many companies, the EU established the Non-Financial Reporting Directive (NFRD) in 2014 and the Corporate Sustainability Reporting Directive (CSRD) in 2022. Both directives have influenced respective Swiss lawmaking. Especially for mid-sized enterprises, further approaching CSRD would involve significant operational challenges. In this article, we summarize and analyze these developments with regard to Switzerland. This includes also the discussion paper «Nachhaltigkeit in der FER» published by the Swiss accounting standard setter.